Are we targeting the right population? Application of eligibility criteria of 10 dementia prevention trials to the general population. (31st December 2021) - Licher, Silvan; Wolters, Frank J; Pavlović, Jelena; Kavousi, Maryam; Leening, Maarten JG; Ikram, M Kamran; Ikram, M Arfan
Abstract: Background: Various trials have investigated the effects of multidomain lifestyle interventions on cognitive decline, but with limited clinical benefit. This could be due to these trials targeting older individuals with elevated cardiovascular risk factors, who often already qualify for preventive intervention. We aimed to determine clinical implications of trials by application of trial eligibility criteria and prognosis to the general population. Method: We conducted a literature review and sought to identify large (≥500 participants), phase‐3 multidomain lifestyle trials for the prevention of cognitive decline or dementia. We extracted eligibility criteria, and applied these to participants from the population‐based Rotterdam Study (40≥years). We determined what proportion of trial‐eligible individuals qualified for preventive intervention according to American (ACC/AHA) and European (ESC/EAS) cardiovascular prevention guidelines. To evaluate whether trial inclusion criteria optimally captured individuals at high risk of dementia that could benefit most, we compared remaining lifetime dementia risk, with 10‐year predicted risks for cardiovascular events. Result: Out of 1448 abstracts, we five identified published dementia prevention trials (DR's EXTRA, FINGER, preDIVA, MAPT and HATICE). Through trial registries, we identified another five (US‐POINTER, MIND‐CHINA, MYB‐Trial, J‐Mint and AgeWell.de) that were ongoing at time of the search. Among 5381 Rotterdam Study participants (mean age 72 years, 58% women), eligibility across published trials ranged from 48% for MAPT to 87% for PREDIVA, largely mimicking estimates from original trial reports. Variability in eligibility was wider for ongoing trials, and ranged from 0.9% for US‐POINTER, to 21% for Age‐Well.de up to 94% for J‐Mint. The vast majority of individuals already qualified for both lifestyle and pharmaceutical interventions (e.g. statins or antihypertensives) based on their cardiovascular risk (ACC/AHA: from 65% for DRs EXTRA to 93% for AgeWell.de, for ESC/EAS: from 60% for DR's EXTRA to 83% for HATICE). Remaining lifetime dementia risk was higher when individuals were at lower 10‐year cardiovascular risk. Conclusion: Multidomain dementia prevention trials target a segment of the population that already qualifies for preventive interventions based on their cardiovascular risk according to cardiology guidelines. These findings call for adapted recruitment strategies in dementia trials, to adequately capture the population at risk in whom maximum benefit can be achieved.